Advanced machine learning methods in psychiatry: an introduction. Issue 2 (16th March 2020) - Wu, Tsung-Chin; Zhou, Zhirou; Wang, Hongyue; Wang, Bokai; Lin, Tuo; Feng, Changyong; Tu, Xin M
Abstract : Mental health questions can be tackled through machine learning (ML) techniques. Apart from the two ML methods we introduced in our previous paper, we discuss two more advanced ML approaches in this paper: support vector machines and artificial neural networks. To illustrate how these ML methods have been employed in mental health, recent research applications in psychiatry were reported.